Predicting Agility Performance with other Performance Variables in Pubescent Boys: A Multiple-Regression Approach. Issue 2 (April 2014) - Sekulic, Damir; Spasic, Miodrag; Esco, Michael R.
The goal was to investigate the influence of balance, jumping power, reactive-strength, speed, and morphological variables on five different agility performances in early pubescent boys ( N = 71). The predictors included body height and mass, countermovement and broad jumps, overall stability index, 5 m sprint, and bilateral side jumps test of reactive strength. Forward stepwise regressions calculated on 36 randomly selected participants explained 47% of the variance in performance of the forward-backward running test, 50% of the 180° turn test, 55% of the 20 yd. shuttle test, 62% of the T-shaped course test, and 44% of the zig-zag test, with the bilateral side jumps as the single best predictor. Regression models were cross-validated using the second half of the sample ( n = 35). Correlation between predicted and achieved scores did not provide statistically significant validation statistics for the continuous-movement zig-zag test. Further study is needed to assess other predictors of agility in early pubescent boys.